NILAI BATAS ANTIGEN NS1 DENGUE KUANTITATIF SEBAGAI PREDIKTOR KEPARAHAN JANGKITAN/TULARAN (INFEKSI) VIRUS DENGUE ANAK - Betty A Tambunan; Aryati . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
The diagnosis of viral dengue infection is very important for the management of dengue patients. In acute phase infection circulatingNS1 antigen can be detected in the sera of patients with dengue viral infection. This study is evaluating the NS1 antigen level in denguepatients using antigen captured ELISA Platelia TM Dengue NS1 Ag (Bio-Rad Laboratories). In this 30 examined dengue patients consistingof 3(10%) undifferentiated fever, 10(33.33%) dengue fever, 12(40%) DHF grade I, 2(6.66%) DHF grade II, 2(6.66%) DHF gradeIII, 1(3.33%) DHF grade IV. The result revealed that NS1 antigen was positive in 12 among 30 patients (40%) which were diagnosedas Dengue Viral infection based on 1997 WHO criteria. The sensitivity of NS1 antigen in these patients as confirmed with IgM andIgG antidengue serology test was 52.2%. The highest positivism of NS1 antigen was on the third day of fever. The results analyzed bySpearman correlation test revealed that there was no significant correlation between NS1 antigen level and the severity of dengue viralinfection. The cut-off value of quantitative NS1 antigen could not be determined because they were no significant correlation shown forNS1 antigen as the predictor for the severity of dengue viral infection. The conclusion of the study so far shown that the quantitativeNS1 antigen level could not be used as the predictor for the severity of dengue viral infection. The cut-off value of quantitative NS1antigen could not be determined because there were no significant correlation shown for NS1 antigen as the predictor for the severityof dengue viral infection.